PELI1 in human cancers: a pan-cancer exploration of its molecular function, clinical significance, and immunomodulatory roles - Xu, Yan; Zhou, Jiale; Chen, Xiaoran; Dong, Xiaoqing; Chen, Bing (Frontiers in Immunology, 2026)
IntroductionThe E3 ubiquitin ligase Pellino1 (PELI1) is ubiquitously expressed in human tissues and primarily modulates inflammatory and immune responses; however, its pan-cancer biological significance remains poorly characterized.MethodsWe employed a combination of R software and online bioinformatics platforms—including UALCAN, HPA, GEPIA2, cBioPortal, STRING, TISIDB, SRAMP, LinkedOmics, and Sangerbox—to systematically characterize PELI1 in human tumors. Our analyses encompassed its abnormal expression, genetic alterations, prognostic and diagnostic relevance, and epigenetic regulation. Focusing on liver hepatocellular carcinoma (LIHC), we further explored the oncogenic functions of PELI1, its associated signaling pathways, and immunomodulatory roles. Key bioinformatic predictions were subsequently validated through in vitro experiments using LIHC cell lines, including functional assays (proliferation, apoptosis, and cell cycle) and signaling pathway analyses.ResultsPELI1 was frequently overexpressed across multiple tumor types and mainly correlated with poor patient prognosis. The highest frequency of PELI1 alterations was observed in patients with diffuse large B-cell lymphoma, primarily in the form of copy number amplification, while R145Q/W represented the most recurrent mutation sites. PELI1 may drives cancer progression through epigenetic regulation involving DNA methylation and N6-methyladenosine (m6A) RNA modifications. PELI1 could potentially serve as a novel biomarker for diagnosing different cancer types. In LIHC specifically, PELI1 expression was significantly elevated compared to adjacent non-tumor tissues. Functional studies revealed that PELI1 modulated cell apoptosis, cell cycle progression, immune responses and the MAPK-ERK pathway in LIHC. Furthermore, PELI1 may regulate immune checkpoints to influence the immune responses. PELI1 expression was positively correlated with the IC50 of hepatocellular carcinoma investigational drug–CFI-402257. Experimental knockdown of PELI1 in LIHC cell lines suppressed proliferation, promoted apoptosis and induced G1-phase cell cycle arrest via MAPK-ERK pathway.ConclusionsThis pan-cancer study revealed the diagnostic, prognostic and immunomodulatory potential, along with the biological function and mechanism of PELI1, supporting its role as a promising therapeutic target in LIHC.